Ultrasensitive fiber optic inclinometer based on dynamic Vernier effect using push-pull configuration - Wang, Shun (2022)
A push-pull demodulation method is used to create an ultrasensitive fiber optic inclinometer based on the dynamic Vernier effect. To demonstrate this new method, two Fabry Perot interferometers (FPIs) in parallel are employed to constitute the optical Vernier effect. Unlike the traditional Vernier effect, in which one interferometer serves as a reference and the other as a sensor, both interferometers in this design participate in sensing measurement simultaneously. The two external FPIs are constructed on opposite sides of a pendulum, the so-called push-pull configuration, ensuring the extension of one FPI and compression of the other simultaneously. Although the carrier signal is maintained constant, the envelope signal manifests a dynamic enhanced Vernier effect for inclination sensing, while reducing the effect from external disturbance. As a result, an ultrahigh inclination sensitivity of 35.96 nm/° is obtained with a resolution of 2.78× 10-5°, i.e., ∼ 0.5μ rad. In addition, the proposed scheme provides a useful alternative for many sensing applications, given its capability of improving measurement sensitivity and reducing external interference.